Boston Jacky : being an account of the further adventures of Jacky Faber, taking care of business - Meyer, L. A. (Louis A.), 1942- (Meyer, L. A. (Louis A.), 1942- Bloody Jack adventure., 2013)
The irrepressible Jacky Faber, recently arrived in Boston, finds herself at odds with the Women's Temperance Union and local residents angry at the arrival of hundreds of Irish immigrants on a ship owned by Faber Shipping Worldwide.